Entre a caridade e o patrimônio: a oblação de crianças aos cenóbios e mosteiros no reino hispano-visigodo de Toledo do século VII - Frighetto, Renan (2020)
Childhood studies in the late-ancient world have always been related to family history. Such integration ended up launching analyzes on the participation of children in legal and patrimonial terms into oblivion, something that both the civil and ecclesiastical legislative documentation contradict. In addition to the issues surrounding heritage and which are of essential socio-political importance in the context of the Hispanic-Visigoth kingdom of Toledo in the seventh century, we highlight the offering action on the part of parents or relatives of their children, a practice known as monastic oblatio. When offered to monastic communities at an early age, oblates did so without their consent, which ended up causing future problems, such as the attempt to abandon monastic life, something completely prohibited by ecclesiastical and secular authorities. In this study we sought to observe an interesting change in the legal paradigm that allowed the oblate to choose whether he wanted to remain in the monastic condition, an innovation that presents Hispano-Visigoth legislation as updated in that historical context in relation to the Roman legal and cultural tradition.